Bad Guys in Let the games begin! - Blabey, Aaron (New York Scholastic Inc., 2023)
"OK. It's time to stop messin' around...In this book, the One IS going to be reunited with the Others. You ARE going to actually meet the REAL DREAD OVERLORD SPLAARGHON. And ONE CHARACTER is going to change EVERYTHING you thought you knew. This is the one you've been waiting for!"--
"Now a major motion picture from Dreamworks"--Cover.
111976
Keywords: Bad Guys (Fictitious characters) -- Comic books, strips, etc -- Juvenile fiction; Good and evil -- Comic books, strips, etc. -- Juvenile fiction; Superheroes -- Comic books, strips, etc. -- Juvenile fiction; Villains -- Comic books, strips, etc. -- Juvenile fiction; Humorous stories; Juvenile Fiction -- Comics & Graphic Novels -- Animals; Juvenile Fiction -- Comics & Graphic Novels -- Superheroes; Comics (Graphic works); Graphic novels; Humorous comics; Humorous fiction; Superhero comics